Enhancing Cybersecurity in Smart Grids: False Data Injection and Its Mitigation - Unsal, Derya Betul; Ustun, Taha Selim; Hussain, S. M. Suhail; Onen, Ahmet; Suhail Hussain, S.M. (MDPI, 2021)
Integration of information technologies with power systems has unlocked unprecedented opportunities in optimization and control fields. Increased data collection and monitoring enable control systems to have a better understanding of the pseudo-real-time condition of power systems. In this fashion, more accurate and effective decisions can be made. This is the key towards mitigating negative impacts of novel technologies such as renewables and electric vehicles and increasing their share in the overall generation portfolio. However, such extensive information exchange has created cybersecurity vulnerabilities in power systems that were not encountered before. It is imperative that these vulnerabilities are understood well, and proper mitigation techniques are implemented. This paper presents an extensive study of cybersecurity concerns in Smart grids in line with latest developments. Relevant standardization and mitigation efforts are discussed in detail and then the classification of different cyber-attacks in smart grid domain with special focus on false data injection (FDI) attack, due to its high impact on different operations. Different uses of this attack as well as developed detection models and methods are analysed. Finally, impacts on smart grid operation and current challenges are presented for future research directions.
Unsal, Derya Betul/0000-0002-7657-7581; Ustun, Taha Selim/0000-0002-2413-8421; Hussain, S. M. Suhail/0000-0002-7779-8140; Onen, Ahmet/0000-0001-7086-5112;
Keywords: Smart Grid Cybersecurity; False Data Injection; Power System Operation; Power System Protection; Cybersecurity Attacks; Intruder Detection; Cybersecurity For Scada Systems